har 2019
DOI: 10.35248/har.2019.8.8
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of growing old: A lifeworld hermeneutic study on existential matters during the third age of life

Abstract: Dalheim-Englund aThis study investigates existential matters in the third age of life, which encompasses the years after retirement and ends when extensive support needs emerge in the fourth age. As the theoretical starting point in a lifeworld hermeneutic approach, 18 healthy older adults were interviewed about what it means for them to grow old. The interviews were interpreted according to Gadamer's principles of openness and Ricoeur's proposal to provide suggestions on how meaning can be explained. The find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Researchers have extensively explored issues around shared identities from a wide range of traditions and perspectives including ethnicity and feminism-based research, sometimes referred to as the insider/outsider perspective (Aiello & Nero, 2019). Palmér, et al (2019) observed that it is difficult to avoid the existential fact that we are part of the world that we study. This has led to the subsequent development of what has come to be known as researcher reflectivity (Aiello & Nero, 2019) which recommends working towards better understanding of the role of the researcher and the impact of the research processes on the research findings.…”
Section: Insider/outsider Researcher Impactmentioning
confidence: 99%
“…Researchers have extensively explored issues around shared identities from a wide range of traditions and perspectives including ethnicity and feminism-based research, sometimes referred to as the insider/outsider perspective (Aiello & Nero, 2019). Palmér, et al (2019) observed that it is difficult to avoid the existential fact that we are part of the world that we study. This has led to the subsequent development of what has come to be known as researcher reflectivity (Aiello & Nero, 2019) which recommends working towards better understanding of the role of the researcher and the impact of the research processes on the research findings.…”
Section: Insider/outsider Researcher Impactmentioning
confidence: 99%
“…Although it seems reasonable to believe that life for individuals during old age is just as diverse as for those of younger age, the finality of life may be neglected earlier in life. Generally, one acknowledges the finality of life by being part of a generation that successively disappears (se for example Dalheim-Englund et al., 2018 ; Palmér et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The older we become, the closer death is, but, according to Van Orden et al ( 2014 ), there is no reason to believe that older adults generally think about death and dying. Palmér et al ( 2018 ) found that older adults who reflect on the last part of life during in-depth interviews talk freely about how to reach a worthy end of life and, in particular, how to avoid dying with extreme suffering. Such thinking about a worthy end of life entails acknowledging death.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations